FROM INDO-PACIFIC CENTRALITY TO STRATEGIC AUTONOMY: ASEAN – US PERSPECTIVE - Hino Samuel Jose (Indonesian Association for International Relations, 2022)
Indo-Pacific is indeed a versatile region with vast geoeconomic and geopolitical advantages and potentials, with ASEAN at its center. Strategic engagement of countries whether to bandwagon or balance major power’s rivalries are pretty much a pertinent deliberation for the last and next decades to come as the global shifting is now moving towards the Indo-Pacific region. This paper employs qualitative analysis to answer the main contentions of: (1) how minilateralism affects Indo-Pacific, and what ASEAN-US role can be explored; and (2) does ASEAN-US matter and how it could actively find convergences in navigating forward in the rules-based region. The author suggests that looking west and being concerned the east or the other way around can be a sufficient strategy in constructing ASEAN-US engagement amid the rising minilateral groupings and concerns against the “crippled” ASEAN centrality since AUKUS and the recent developments in the region.